Farmers’ seed production in organic horticulture in NW Portugal - Wallner, Verena (2020)
Organic agriculture aims to provide organic farmers with organic seed. The EU regulation on organic agriculture supports this aim by implying the obligatory use of organic seed and planting material. Nevertheless, derogations for using un-treated GMO-free non organically produced seeds are granted, because organic seed is not sufficiently available and an absolute restriction would impede organic farmers in terms of diversity and competition. The aim of this paper is to identify the importance of organic farmers’ seed production in organic horticulture using a study case conducted in NW Portugal.